Blood lactate response and critical speed in swimmers aged 10-12 years of different standards - Denadai, B. S.; Greco, C. C.; Teixeira, M. (Journal of Sports Sciences, 2000)
It has previously been shown that measurement of the critical speed is a non-invasive method of estimating the blood lactate response during exercise. However, its validity in children has yet to be demonstrated. The aims of this study were: (1) to verify if the critical speed determined in accordance with the protocol of Wakayoshi et al. is a non-invasive means of estimating the swimming speed equivalent to a blood lactate concentration of 4 mmol·l-1 in children aged 10-12 years; and (2) to establish whether standard of performance has an effect on its determination. Sixteen swimmers were divided into two groups: beginners and trained. They initially completed a protocol for determination of speed equivalent to a blood lactate concentration of 4 mmol·l-1. Later, during training sessions, maximum efforts were swum over distances of 50, 100 and 200 m for the calculation of the critical speed. The speeds equivalent to a blood lactate concentration of 4 mmol·l-1 (beginners = 0.82 ± 0.09 m·s-1, trained = 1.19 ± 0.11 m·s-1; mean ± s) were significantly faster than the critical speeds (beginners = 0.78 ± 0.25 m·s-1, trained = 1.08 ± 0.04 m·s-1) in both groups. There was a high correlation between speed at a blood lactate concentration of 4 mmol·l-1 and the critical speed for the beginners (r = 0.96, P < 0.001), but not for the trained group (r = 0.60, P > 0.05). The blood lactate concentration corresponding to the critical speed was 2.7 ± 1.1 and 3.1 ± 0.4 mmol·l-1 for the beginners and trained group respectively. The percent difference between speed at a blood lactate concentration of 4 mmol·l-1 and the critical speed was not significantly different between the two groups. At all distances studied, swimming performance was significantly faster in the trained group. Our results suggest that the critical speed underestimates swimming intensity corresponding to a blood lactate concentration of 4 mmol·l-1 in children aged 10-12 years and that standard of performance does not affect the determination of the critical speed.